2018
DOI: 10.21873/anticanres.12471
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Symptom Burden, Rate of Completion of Palliative Radiotherapy and 30-day Mortality in Two Groups of Cancer Patients Managed With or Without Additional Care by a Multidisciplinary Palliative Care Team

Abstract: The MPCT group was characterized by a higher symptom burden. Prognostic factors such as performance status were not balanced between the two groups. Despite this fact, actuarial overall survival was comparable. Given the high rate of 30-day mortality in the MPCT group, efforts to optimize criteria for initiation of radiotherapy are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Similarly, in the second study, the authors compared patients undergoing PRT as part of normal clinical practice with subjects managed as part of a multidisciplinary palliative care team. Despite the fact that the second group included significantly more patients with reduced performance status and with higher Edmonton symptom assessment system symptom scores (particularly in terms of pain, fatigue, anxiety, and depression), the actuarial overall survival was comparable among the two patients populations and also the rate of PRT during the last month of life was comparable [ 25 ]. Finally, Spedicato et al reported on an Italian home care experience, which began in the 1990s, for terminally ill cancer patients receiving supportive care by a team of ROs, nurses and psychologists.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in the second study, the authors compared patients undergoing PRT as part of normal clinical practice with subjects managed as part of a multidisciplinary palliative care team. Despite the fact that the second group included significantly more patients with reduced performance status and with higher Edmonton symptom assessment system symptom scores (particularly in terms of pain, fatigue, anxiety, and depression), the actuarial overall survival was comparable among the two patients populations and also the rate of PRT during the last month of life was comparable [ 25 ]. Finally, Spedicato et al reported on an Italian home care experience, which began in the 1990s, for terminally ill cancer patients receiving supportive care by a team of ROs, nurses and psychologists.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in most analyzed studies no details on dose and fractionation of the PRT were reported. Only Nieder et al, in their comparisons between PRT alone or integrated in multidisciplinary management, reported that PRT was delivered with hypofractionated regimens (from 8 Gy × 1 fraction to 3 Gy × 10 fractions), [ 24 , 25 ] while Ishii et al, in their series of esophageal tumors, used a conventional fractionation (40–60 Gy in 2 Gy/fraction) [ 32 ]. However, it should be emphasized that all reports uniformly showed some advantages from integrating PRT with supportive care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palliative radiotherapy (PRT) is among the cornerstones of oncological approaches in patients with incurable cancer (1). In our institution, which has a dedicated PRT program that serves a small and scattered population of less than 200,000 inhabitants in rural North-Norway (large parts of Nordland County with a total of population of 243,000), overtreatment and 30-day mortality (30DM) has long been a topic of research (2)(3)(4)(5)(6). The first comprehensive analysis related to the time period 2007-2009 (7).…”
mentioning
confidence: 99%